Sexual minority young adults' perspectives on how minority stress and other factors negatively affect self-esteem: a qualitative interview study. (19th May 2022) - Bridge, Livia; Smith, Patrick; Rimes, Katharine A.
Abstract: Sexual minority young adults (lesbian, gay and bisexual), are at increased risk of experiencing mental health problems than their heterosexual peers. On average they also have lower self-esteem which may contribute to the development or maintenance of mental illnesses. Interventions to improve self-esteem could improve well-being and reduce mental ill-health risk in sexual minority young adults. It is important to understand the processes that contribute to lower self-esteem in this population. The present study aimed to explore these processes. Semi-structured qualitative interviews were conducted with a sample of 20 sexual minority young adults (age 16–24 years) with a range of self-esteem levels. Using thematic analysis, three overarching areas were idenitified: 'Negative social evaluations and reduced belonging', 'Striving and failing to meet standards', and 'Negative sexual orientation processes'. These findings have theoretical implications for minority stress models of mental health inequalities, highlighting the potential interaction between minority-specific and more general risk factors for mental health problems. Findings also have clinical implications for the development of tailored interventions to help improve low self-esteem in sexual minority young adults.